2020
DOI: 10.1016/j.euros.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Wharton's Jelly-derived Mesenchymal Stem Cells on Renal Fibrosis in Rats with Unilateral Ureteral Obstruction

Abstract: Background Renal failure is a global medical problem. The use of mesenchymal stem cells (MSCs) for preservation and regeneration of renal tissue in acute and chronic kidney diseases has recently been the focus of investigation. Objective To evaluate the protective effect of MSC injections in a rat model of kidney obstruction. Design, setting, and participants We assigned 15 male Wistar rats to three separate groups: the normal group underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Furthermore, we reported significant improvement in renal function parameters, including serum creatinine, BUN, urinary proteins, and kidney morphology in the WJ-MSCs group, suggesting and confirming the renoprotective effect of the WJ-MSCs on renal IRI injury. These findings agreed with previous experimental studies that demonstrated the effectiveness of using stem cell therapy against renal IRI injury [9,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we reported significant improvement in renal function parameters, including serum creatinine, BUN, urinary proteins, and kidney morphology in the WJ-MSCs group, suggesting and confirming the renoprotective effect of the WJ-MSCs on renal IRI injury. These findings agreed with previous experimental studies that demonstrated the effectiveness of using stem cell therapy against renal IRI injury [9,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…Umbilical cord-derived MSC, specifically the stem cells harvested from Wharton's Jelly, demonstrate promise for future clinical applications because of their limited heterogeneity and easy accessibility in numerous tissues [291,292]. Compared to bone marrow-derived MSC, umbilical cord-derived MSC have lower immunogenicity and superior ability to proliferate and differentiate, and they can be isolated without any invasive surgical procedure and manufactured in large quantities without compromising potency [289,293,294].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%